Descomplicando a ciência e a tecnologia para esclarecer e perguntar ao pecuarista fluminense tudo sobre a raiva rural - Meireles, M. A. D.; Pereira, S. R. F. G.; Bernardo-Pedro, T.; Florido, V. A.; Oliveira, A. C.; Linhares, J. M.; Vieira, L. F. P.; Chicarino, C. N. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2011)
Rabies is a contagious disease of great interest to the livestock and public health. The etiologic agent is a neurotropic virus (family Rhabdoviridae and genus Lyssavirus), which affects the central nervous system. The disease has an anthropozoonotic character, and all mammals may be infected and develop it. Rabies affects domestic herbivores (livestock), and its main transmitter, in rural areas, is the “common vampire bat”, Desmodus rotundus. This research aimed at education in health and surveillance of rabies, in a simple and playful, to the cattle ranchers of the Northern and Northwestern regions of Rio de Janeiro State, clarifying aspects about rural rabies. The following municipalities/ locations were visited: Batatal, Boa Vista, Cardoso Moreira, Caxeta, Dores de Macabu, Espírito Santinho, Hatobá, Italiana, Italva, Pedra Santa, Santa Maria São Francisco de Itabapoana and Vila Nova. Both Emater-Rio and Núcleo de Defesa Agropecuária (NDA) of Campos dos Goytacazes, RJ, participated in all visits. A total audience of over 100 farmers, including producers (ranchers) and rural workers (animal handlers), were served. The theme was approached by means of folders, lectures and questionnaires to the target audience. The following data was revealed: 20% of the producers reported suspected cases of rabies on their property, in the last five years; of these, 50% did not send samples for laboratory examination. 74% reported the presence of bats on their property and 75% noticed signs of aggression in animals. Towards the control of bats, 30% of the producers searched for their shelters to exterminate the colonies, 20% were applying the “vampiricid topic” on attacked animals and 60% sought their NDA. Regarding the transmission of rabies, 75% believed that only the vampire bats could do it, 15% believed that human beings may not contract the disease and 70% knew which animals could convey it. In suspected cases of rabies, 60% of the producers contacted the NDA, 35% slaughtered the sick animals and 5% tried to treat them. As regards rabies vaccination, 20% have never used the vaccine and 80% vaccinated their flock; of these, 50% semiannual, 43.3% yearly and 6.2% in the outbreaks. Rural rabies has been emerging due to lack of vaccination and increasing bat attacks. The lack of knowledge and even negligence on the part of producers should be considered. Leading information to the cattle rancher is the best way for prevention and control of rural rabies. As greater as the number of people served, the lower was the losses caused in the livestock economy and the risks to human beings.